Variability of Ground Motion Amplitudes Recorded in Bucharest Area during Vrancea Intermediate-Depth Earthquakes - Florin Pavel (Hindawi Limited, 2021)
This study focuses on the assessment of the correlation and variability of ground motion amplitudes recorded in Bucharest area during Vrancea intermediate-depth earthquakes from a database of 119 pairs of horizontal components. Empirical models for the evaluation of the peak ground velocity and displacement from spectral accelerations are proposed in this study. The distribution of the shear wave velocities from 41 boreholes at specific depths appears to follow a normal probability distribution. The analysis performed in this study has also shown that the variability of peak ground velocities and displacements does not appear to be influenced by the earthquake magnitude. In addition, it was observed that the variability in terms of shear wave velocities at specific depths is smaller than the variability of the spectral amplitudes of the recorded ground motions. The empirical site-amplification factors from the Eurocode 8 draft fail to capture the long-period spectral amplifications observed in Bucharest area during large magnitude Vrancea intermediate-depth earthquakes.